3D Bioplotting of Gelatin/Alginate Scaffolds for Tissue Engineering: Influence of Crosslinking Degree and Pore Architecture on Physicochemical Properties. Issue 9 (September 2016) - Pan, Ting; Song, Wenjing; Cao, Xiaodong; Wang, Yingjun
Abstract : Gelatin/Alginate hydrogels were engineered for bioplotting in tissue engineering. One major drawback of hydrogel scaffolds is the lack of adequate mechanical properties. In this study, using a bioplotter, we constructed the scaffolds with different pore architectures by deposition of gelatin/alginate hydrogels layer-by-layer. The scaffolds with different crosslinking degree were obtained by post-crosslinking methods. Their physicochemical properties, as well as cell viability, were assessed. Different crosslinking methods had little influence on scaffold architecture, porosity, pore size and distribution. By contrast, the water absorption ability, degradation rate and mechanical properties of the scaffolds were dramatically affected by treatment with various concentrations of crosslinking agent (glutaraldehyde). The crosslinking process using glutaraldehyde markedly improved the stability and mechanical strength of the hydrogel scaffolds. Besides the post-processing methods, the pore architecture can also evidently affect the mechanical properties of the scaffolds. The crosslinked gelatin/alginate scaffolds showed a good potential to encapsulate cells or drugs.